Evaluation of User Experience in Integrated Learning Information Systems Using User Experience Questionnaire (UEQ) - Arista Pratama; Asif Faroqi; Eka Prakarsa Mandyartha (Journal of Information System and Informatics, 2022)
Information and Communication Technology (ICT) has a role in assisting in monitoring and evaluating the learning process in schools. Integrated Learning Information System is the application of an integrated information system to improve the quality of academic and learning services accessed by all school members (teachers, homeroom teachers, foundations, and students) and parents/guardians of students. The learning information system focuses on making it easier to monitor and evaluate student academic and learning outcomes. User experience measurement is carried out to determine the extent to which the success of user understanding using the system so that the purpose of using the system can be achieved. This study aims to analyze the user experience of the Integrated Learning Information System using the User Experience Questionnaire (UEQ) method. This study uses quantitative data by distributing online questionnaires to 50 students. The results of the evaluation of user experience on learning information systems using the UEQ method state that attractiveness is 2.121, perspicuity is 2.152, efficiency is 2.319, dependability is 1.505, stimulation is 1.716, and novelty is 1.020. This proves that all aspects have positive values. The benchmark results showed that the attractiveness, perspicuity, efficiency, and stimulation aspects were included in the excellent criteria, while the dependability aspect was included in the good criteria and novelty included in the above average criteria.